2018
DOI: 10.1007/s00424-018-2146-8
|View full text |Cite
|
Sign up to set email alerts
|

The function of TRP channels in neutrophil granulocytes

Abstract: Neutrophil granulocytes are exposed to widely varying microenvironmental conditions when pursuing their physiological or pathophysiological functions such as fighting invading bacteria or infiltrating cancer tissue. Examples for harsh environmental challenges include among others mechanical shear stress during the recruitment from the vasculature or the hypoxic and acidotic conditions within the tumor microenvironment. Chemokine gradients, reactive oxygen species, pressure, matrix elasticity, and temperature c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 161 publications
0
26
1
Order By: Relevance
“…Although this proposed mechanism is consistent with the results, it does not consider several other possible interpretations. TRPM2 is indeed expressed by multiple types of innate immune cell (Syed Mortadza et al, 2015), including monocytes (Yamamoto et al, 2008), neutrophils (Heiner et al, 2003;Najder et al, 2018), and microglia (Miyake et al, 2014). Because TRPM2 deletion in the mice by Tsutsui et al (2018) was not specific to macrophages, the contribution of TRPM2 deletion in these other immune cells must be considered, as discussed below.…”
Section: Review Of Tsutsui Et Almentioning
confidence: 99%
“…Although this proposed mechanism is consistent with the results, it does not consider several other possible interpretations. TRPM2 is indeed expressed by multiple types of innate immune cell (Syed Mortadza et al, 2015), including monocytes (Yamamoto et al, 2008), neutrophils (Heiner et al, 2003;Najder et al, 2018), and microglia (Miyake et al, 2014). Because TRPM2 deletion in the mice by Tsutsui et al (2018) was not specific to macrophages, the contribution of TRPM2 deletion in these other immune cells must be considered, as discussed below.…”
Section: Review Of Tsutsui Et Almentioning
confidence: 99%
“…The selectivity of TRP channels has a wide spectrum, ranging from nonselective cation channels to highly selective (Ca 2+ ) channels. TRP channels respond to a variety of stimuli such as: ligands, heat, mechanical stimulation, and play a role in different processes such as intracellular (Ca 2+ ) metabolism, phagocytosis, cell motility, haemostasis, and infl ammation (32)(33)(34). A number of studies revealed the effects of subpopulations of TRP channels on many different cancer cells and the relationship between the survival and the expression of TRP channels in these cancers have been clearly demonstrated (35).…”
Section: Discussionmentioning
confidence: 99%
“…DAG can directly activate members of the transient receptor potential (TRP) channel family, like TRPC6, leading to Ca 2+ influx from the extracellular space [9]. Several Ca 2+ -permeable channels such as Orai1 channels [8,10] as well as TRPC1 [11], TRPC6 [12,13], TRPM2 [14], and TRPV4 channels [15] in neutrophils have been shown to be involved in their recruitment (reviewed in [16,17]). However, the elucidation of the underlying mechanisms by which these Ca 2+ influx channels regulate neutrophil recruitment is complicated by the multitude of chemoattractants.…”
Section: Introductionmentioning
confidence: 99%
“…However, the elucidation of the underlying mechanisms by which these Ca 2+ influx channels regulate neutrophil recruitment is complicated by the multitude of chemoattractants. While there seems to be a coupling between TRPC6 channels and CXCR2, data concerning the link between TRPM2 channels and fMLPtriggered signaling are discussed controversially [16]. It is further complicated by the fact that Ca 2+ signaling in endothelial (or epithelial) cells has to be considered, too.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation